Problem Pelaksanaan Kompetensi Pengadilan Agama Jember Di Bidang Ekonomi Syariah: The Problem of Implementing the Jurisdiction of the Jember Religious Court in the Field of Sharia Economic Law - Muhammad Faisol (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2016)
The expansion of Religious Court authority to include sharia economic disputes under Law No. 3 of 2006 has created a paradoxical situation where the rapid growth of Indonesia's sharia economy contrasts sharply with the extremely low number of cases filed. This study aims to identify the core problems hindering the implementation of this new competence at the Jember Religious Court. Employing a qualitative field research design, data were collected through observation, in-depth interviews with judges, and documentation at the Jember Religious Court, then analyzed using descriptive-qualitative techniques. The findings reveal three main problems: ineffective socialization of the new law to both legal apparatus and the public, legal overlaps particularly between arbitration laws (UU No. 30 of 1999) and sharia banking laws (UU No. 21 of 2008) that create jurisdictional confusion, and low public trust regarding the judges' capacity to handle sharia economic cases. The study concludes that without resolving these systemic legal and social barriers, the expansion of the Religious Court's authority will remain ineffective, and it recommends more intensive legal synchronization and capacity building for judges. Perluasan kewenangan Pengadilan Agama untuk menangani sengketa ekonomi syariah pasca UU No. 3 Tahun 2006 menciptakan situasi paradoksal di mana pertumbuhan ekonomi syariah yang pesat tidak sebanding dengan minimnya perkara yang masuk ke pengadilan. Penelitian ini bertujuan untuk mengidentifikasi problem utama yang menghambat pelaksanaan kompetensi baru tersebut di Pengadilan Agama Jember. Dengan menggunakan pendekatan kualitatif jenis penelitian lapangan, data dikumpulkan melalui observasi, wawancara mendalam dengan hakim, dan dokumentasi, lalu dianalisis secara deskriptif-kualitatif. Hasil penelitian menemukan tiga problem utama: pertama, sosialisasi undang-undang yang tidak efektif; kedua, tumpang tindih sistem perundang-undangan, khususnya antara UU Arbitrase dan UU Perbankan Syariah yang menimbulkan konflik yurisdiksi dan klausul opsional yang melemahkan pengadilan agama; ketiga, rendahnya kepercayaan publik terhadap kapabilitas hakim agama dalam memutus perkara ekonomi syariah. Penelitian ini menyimpulkan bahwa tanpa penyelesaian hambatan hukum sistemik dan sosial tersebut, perluasan kewenangan ini tidak akan berjalan efektif, dan merekomendasikan sinkronisasi hukum serta penguatan kapasitas hakim.